Improve The Numeracy Skills of Fifth-Grade Students Through Self-Efficacy in Elementary Schools - M Ridwan; Muhammad Misbahudholam AR; Fajar Budiyono; Tri Sukitman (Jurnal Ilmiah Sekolah Dasar, 2023)
Numerical ability is the basis for students in working on solving math problems and is one of the indicators for assessing the Minimum Competency Assessment. Based on the PISA results released by the OECD, Indonesia's numeracy literacy level was ranked 74th out of 79 countries, this shows that Indonesia's numeracy literacy level is still very low. This study aims to analyze the numeracy skills of fifth-grade students through self-efficacy in elementary schools. The type of research used is causal-comparative research, also known as ex-post facto research with a quantitative approach. Respondents in this study were 32 grade 5 students. The research instruments used were self-efficacy questionnaires, and numeracy skills test questions. Data analysis in this study used descriptive and inferential statistics in simple linear regression analysis. The research results show that students' self-efficacy can significantly improve their numeracy skills. Students' numeracy skills are influenced by student self-efficacy by 51.2%. Meanwhile, 48.8% is influenced by other factors besides self-efficacy. The results of this study also show that the better the students' self-efficacy, the better their numeracy literacy skills will be.